Diseño y desarrollo de un sistema teleinformatico Experimental - Cardenas C, Roberto (Ingeniería, 1999)
It is described in this article the physical platform and the software development for a net LAN. The interfaz RS-485 is chosen, with which is sought to create a platform that allows the experimentation of protocols, as well as the practical implementation of tele-computer systems. For it, a transceiver is developed that converts the serial port RS-232 in a port net controller that has transmission signs, reception, collision, supervision and control.